Retroperitoneal fibrosis with normal intravenous urogram. Issue 712 (February 1985) - Creagh, F. M.; Stone, T.; Stephenson, T. P.; Lazarus, J. H.
Abstract : A 58 year old male presented with a two week history of low back pain and malaise. The intravenous urogram (IVU) at presentation was normal but within three months he had developed renal failure with bilateral ureteric obstruction on repeat IVU. Primary retroperitoneal fibrosis was confirmed at operation. This case demonstrates that retroperitoneal fibrosis may progress rapidly to renal failure within a few months of the first symptoms. In addition, the IVU may be normal in the early stages of the illness.